Current research progress in targeted anti‐angiogenesis therapy for osteosarcoma. (26th July 2021) - Liu, Yun; Huang, Nenggan; Liao, Shijie; Rothzerg, Emel; Yao, Felix; Li, Yihe; Wood, David; Xu, Jiake
Abstract: Osteosarcoma (OS) is the most common primary malignant bone tumour with a peak in incidence during adolescence. Delayed patient presentation and diagnosis is common with approximately 15% of OS patients presenting with metastatic disease at initial diagnosis. With the introduction of neoadjuvant chemotherapy in the 1970s, disease prognosis improved from 17% to 60%‐70% 5‐year survival, but outcomes have not significantly improved since then. Novel and innovative therapeutic strategies are urgently needed as an adjunct to conventional treatment modalities to improve outcomes for OS patients. Angiogenesis is crucial for tumour growth, metastasis and invasion, and its prevention will ultimately inhibit tumour growth and metastasis. Dysregulation of angiogenesis in bone microenvironment involving osteoblasts and osteoclasts might contribute to OS development. This review summarizes existing knowledge regarding pre‐clinical and developmental research of targeted anti‐angiogenic therapy for OS with the aim of highlighting the limitations associated with this application. Targeted anti‐angiogenic therapies include monoclonal antibody to VEGF (bevacizumab), tyrosine kinase inhibitors (Sorafenib, Apatinib, Pazopanib and Regorafenib) and human recombinant endostatin (Endostar). However, considering the safety and efficacy of these targeted anti‐angiogenesis therapies in clinical trials cannot be guaranteed at this point, further research is needed to completely understand and characterize targeted anti‐angiogenesis therapy in OS. Abstract : Mechanistic insights into the OS targeted anti‐angiogenesis therapy.